Production Development Strategy on Corn (Zea Mays) Commodity in Banten Province Using Process Hierarchy Analysis Method - Ahmad Alfarizy; Mohamad Arief Setiawan; kalfin Kalfin (International Journal of Research in Community Services, 2021)
The increased rate of maize production in Indonesia is relatively slow, on the other hand, the need for corn as raw material for the food industry and faster food improvement. Still, demand for maize for direct consumption during the economic crisis also increased. This study aims to identify corn development strategy in Banten Province and formulate priority scale efforts for corn commodity development strategy in Banten province.  The type of this research is qualitative with a descriptive approach, with the research location taken intentionally (purposive). The in Banten Province, then prioritize the strategy to improve and expand the marketing network in the form of fruit and corn processing products (corn kernels) through the program of local superior product introduction to outsiders of Banten Province. The priority of the fifth development strategy is to increase cooperation between farmers, processing industries, and traders with the government. The sampling technique used the purposive sampling method with 52 respondents consisting of farmers, the processing industry, traders, and the government. Data analysis using Analytic Hierarchy Process and Focus Group Discussion. The result of this research is the alternative development strategy of 25 strategies which are all obtained through Focus Group Discussions and Analytic Hierarchy Process method, then get the strategy priority scale, the priority strategy to improve corn cultivation technique in Banten Province, then the priority of strategy improvement of facilities and infrastructure. The priority of further development strategy is to improve the quality and quantity of maize.